História e construção social do currículo de ciências na educação básica : um olhar sobre o ensino fundamental nas escolas municipais de Rio Bananal/ES - Fanchiotti, Katia Demuner (2024)
This research sought to identify how the Science curriculum in the city of Rio Bananal/ES was arranged, over the last decade and the first years of the current decade, with a view to student training and their reflection on the history of Science teaching. The main objective was to understand the historical process, within the last decade, of the development of the Science curriculum in the municipality of Rio Bananal/ES. To this end, qualitative research was carried out involving bibliographic and documentary analysis in the following sources: Legislation, Curricular Guidelines and Teaching Plans for the Science subject, available at the Regional Education Superintendency, Municipal Education Department and in the Teaching Units themselves. Furthermore, a semi-structured interview was carried out with teachers who teach the Science subject in schools that offer full Elementary Education in the municipality of Rio Bananal/ES. Thus, when analyzing the history of Science teaching in the municipality of Rio Bananal/ES, we can assert that this educational ideology has a strong influence from state policy, in addition to that which comes from the teachers themselves who work in municipal schools